Direct Correlation of the Organic Solar Cell Device Performance to the In‐Depth Distribution of Highly Ordered Polymer Domains in Polymer/Fullerene Films. Issue 11 (21st June 2013) - Engmann, Sebastian; Singh, Chetan R.; Turkovic, Vida; Hoppe, Harald; Gobsch, Gerhard
Abstract This study correlates the device performance of organic solar cells and the electronic charge transport within polymer/fullerene films, directly to the optical order of the polymer. The optical order was measured by spectroscopic ellipsometry and evaluated by our previously derived model. We were able to determine the in‐depth distribution of higher and lower ordered poly(3‐hexylthiophene) (P3HT) domains within an [6, 6]‐phenyl‐C61‐butyric acid methyl ester (PCBM) matrix. The over the film thickness integrated volume fraction of highly ordered P3HT domains could be directly correlated to the corresponding solar cell device performance. We are able to describe various thermally annealing conditions between room‐temperature and 200 °C.